Organoleptic and Qualitative Test of Borax Content in Meatballs and Cilok in Lakasantri Surabaya: Uji Organoleptis dan Kualitatif Kandungan Boraks pada Bakso dan Cilok di Lakasantri Surabaya - Dewi Yuliani Setianingsih; Cicik Herlina Yulianti (Journal Pharmasci (Journal of Pharmacy and Science), 2022)
Meatballs and cilok are favorite’s food in public. Based on market surveys, it turns out that there are still foods containing dangerous preservatives like borax. Borax is a toxic material and can poison cells if ingested in large quantities. The purpose of this study was to determine the organoleptic characteristics of meatballs and cilok stored for 3 days at room temperature. In addition, to determine the presence or absence of borax in meatballs and cilok, a qualitative test was carried out using a borax rapid test kit. This research method was carried out by organoleptic and qualitative testing of meatball and cilok samples obtained around SMPN 28 Lakasantri, Surabaya. Sampling was done by total sampling method. Based on the number of meatball and cilok traders around SMPN 28 Lakasantri Surabaya, there were 5 meatball traders and 5 cilok traders with a total of 10 samples. Then, organoleptic and qualitative tests were carried out using a borax rapid test kit. The results showed that the meatball and cilok samples obtained around SMPN 28 Lakasantri Surabaya after being stored for three days at room temperature, experienced a decrease in quality in the form of a softer texture, a duller color and some even started to grow mold and mildew, and a rotting smell. Meanwhile, based on a qualitative test on all samples of meatballs and cilok using a borax rapid test kit, the results were negative.